Surgical management of the urogenital problem in male cattle - Melkamu Birhanu Meharu (International Journal of Veterinary Science and Research - Peertechz Publications, 2022)
Obstructive urolithiasis is urine retention due to the calculi lodgment in the urinary tract. Thus, treatment of urolithiasis is basically to establish normal urinary passage, which can be accomplished in various ways depending on the severity of the condition. This case report describes surgical management of urolithiasis through penile amputation in a five-year-old local breed bull that was brought to the Veterinary Teaching Hospital of the Addis Ababa University, Bishoftu Ethiopia with a complaint of difficulty in passing urine that had developed certain days before presentations. Upon presentation, the animal was found to be dull and depressed, and tail wringing, stamping the feet, kicking at the abdomen, and stretching were observed. On clinical examination per rectal palpation, the urinary bladder was distended. Based on the history and rigorous clinical examination the case was tentatively diagnosed as obstructive urolithiasis. Then penile amputation was performed through a post-scrotal approach after aseptic preparation and controlling of the animal in the appropriate position. Fortunately, after surgery, the animal was urinated continuously and postoperative follow-up and complications were recorded. Finally, the bull was uneventfully recovered and the skin suture was removed on the 15th day of the operation.